2011
DOI: 10.1175/2010jamc2662.1
|View full text |Cite
|
Sign up to set email alerts
|

A TRMM-Based Tropical Cyclone Cloud and Precipitation Feature Database

Abstract: The Tropical Rainfall Measuring Mission (TRMM) satellite has provided invaluable data for tropical cyclone (TC) research since December 1997. The challenge, however, is how to analyze and efficiently utilize all of the information from several instruments on TRMM that observe the same target. In this study, a tropical cyclone precipitation, cloud, and convective cell feature (TCPF) database has been developed by using observations of the TRMM precipitation radar (PR), Microwave Imager (TMI), Visible and Infrar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 58 publications
2
11
0
Order By: Relevance
“…TC precipitation features were identified if the distance between the centroids of rainfall polygons and TC track on that day is less than 550 km (Figure 1(a)). This method, also utilized by Jiang et al (2011) to identify precipitation features belonging to TCs as detected using satellite data, ensures that rainfall produced by a TC is included if it occurs more than 550 km from the storm track so long as the centroid of the rainfall region falls within 550 km of the storm track. On a day when precipitation produced by a TC and a nearby front became merged, all of this rainfall was included in our study as there is not a way to distinguish the rainfall belonging to each system.…”
Section: Methodsmentioning
confidence: 99%
“…TC precipitation features were identified if the distance between the centroids of rainfall polygons and TC track on that day is less than 550 km (Figure 1(a)). This method, also utilized by Jiang et al (2011) to identify precipitation features belonging to TCs as detected using satellite data, ensures that rainfall produced by a TC is included if it occurs more than 550 km from the storm track so long as the centroid of the rainfall region falls within 550 km of the storm track. On a day when precipitation produced by a TC and a nearby front became merged, all of this rainfall was included in our study as there is not a way to distinguish the rainfall belonging to each system.…”
Section: Methodsmentioning
confidence: 99%
“…Although some studies have examined the diurnal cycle of TC rainfall over the oceans (e.g., Bowman & Fowler, ; Jiang et al, ; Leppert & Cecil, ; Wu et al, ) and have found a predominant nocturnal or early morning rainfall peak, the diurnal cycle of TC precipitation has yet to be fully explored. This is especially true for TCs that are close to sizable landmasses, and there is some disagreement among the observational studies regarding such details as whether there is a single diurnal peak or two peaks and the timing of precipitation maxima (Bowman & Fowler, ; Dunion et al, ; Frank, ; Jiang et al, ; Matyas, ). Several mechanisms have been proposed to explain the TC diurnal cycle, which is ultimately attributed to radiative impacts including cloud–radiation interaction (Melhauser & Zhang, ; Tang et al, , ; Tang & Zhang, ).…”
Section: Introductionmentioning
confidence: 99%
“…By providing consistent spatial coverage with subdaily temporal resolution, satellite rainfall estimates allow the opportunity to quantify the global TC contribution over large continental areas and basins around the world. Using over a decade of satellite rainfall estimates from the Tropical Rainfall Measuring Mission (TRMM), recent studies have investigated the global rainfall contribution for TC basins around the world [Jiang and Zipser, 2010;Jiang et al, 2011]. Similarly, the recent development of hurricane databases for all TC regions [Kossin et al, 2007;Knapp et al, 2010] facilitates the characterization of TC activity and provides a consistent data set to assess TCrelated rainfall for the different basins.…”
Section: Introductionmentioning
confidence: 99%
“…This data product provides 3 hourly rainfall estimates at a spatial resolution of 0.25 Â0.25 [Huffman et al, 2007]. While more general studies [Jiang and Zipser, 2010;Jiang et al, 2011], focused on global TC contribution to total rainfall regardless of land/ocean and regional considerations, this study provides the global contribution of TCs to the annual precipitation budget over land for the period 1998-2009.…”
Section: Introductionmentioning
confidence: 99%